Water Quality Characteristic of Ciliwung River at Bogor Botanical Garden Segmen, Bogor - Aditya Bagus Sujati; Agus Priyono; Siti Badriyah Rushayati (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Ciliwung river is a river with water quality classified in moderate poluted until heavy polluted due to the high pollution load and lack of open green space in river banks, except in some area including Bogor Botanical Garden (KRB). Bogor Botanical Garden (KRB) is one of the open green space that play a rule of buffer area for Ciliwung River in KRB segment. The results of this research by analyzing the water quality (physico-chemical factors and macrozoobenthos) on the inlet KRB, middle KRB and outlet KRB showed that Ciliwung river in KRB segment still meet water quality standard class II except COD. Macrozoobenthos community structure is dominated by the order Ephemeroptera and Trichoptera. Analysis of water quality using Water Quality Index, Pollution Index, Shannon-Wiener diversity index and Hilsenhoff Biotic Index shows there are increasing of the quality of water from the inlet KRB, middle KRB to the outlet KRB.Keywords: green open space, macrozoobenthos, purification